EXPLORING THE EFFECTS OF WORK MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT THE BANDAR LAMPUNG MIDDLE TAX SERVICE OFFICE - Mega, Fredy Ziekrian; Haninun, Haninun; Rahayu, Ni Putu Widhia (Program Studi Magister Manajemen, 2024)
The purpose of this study was to assess: (1) the impact of work motivation on employee performance at KPP Madya Bandar Lampung, (2) the effect of organizational culture on employee performance, and (3) the combined influence of work motivation and organizational culture on employee performance. The study used multiple linear regression and included a sample of 52 employees from the Madya Tax Service Office. Data was collected through observation, questionnaires, and documentation, and analyzed using qualitative and quantitative methods. The results indicated that work motivation positively and significantly affects employee performance, highlighting its importance in enhancing the performance of tax employees. Additionally, organizational culture also positively influences employee performance, suggesting that a strong culture can improve employee behavior and foster a supportive internal climate.